Islam, Food, and Health (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
This research aims to study Islam, food and health in an integrated manner based on a literature approach. This research is descriptive research using a literature study approach to 25 articles related to Islam, food and health. Articles were selected based on inclusion and exclusion criteria. The tool used to search for this article is Publish or Perish . The results of this research show that Islam, food and health are things that cannot be separated from each other. Islam clearly regulates halal and haram food and drink, as well as eating and drinking etiquette. Halal labeling and Islamic branding influence interest in buying food and drinks, both local and imported. Halal food will make the body healthy. In Islam, health is one of the things that Allah loves. Allah loves his servants who are healthy and strong. Prayer, fasting, napping, reading al-Qur’an, and exercising are some forms of Islamic teachings that are useful for physical and spiritual/mental health
Keywords: Islam; Kesehatan; Makanan